Profile of Physical Fitness Level in Class X Students of SMA Pembangunan V Yapis Waena - Doan Adimapita; Andi Syaiful; Marsuki (Classroom Experiences, 2023)
This study aims to describe the profile of physical fitness level in grade X students at SMA Pembangunan V Yapis Waena. The research was conducted with a quantitative descriptive approach, collecting data from 21 grade X students selected by simple randomization, consisting of 11 male students and 10 female students. Data on physical fitness was collected through fitness tests which included running tests, jumping tests, push-up tests, and sit-ups. The research data were analyzed by quantitative descriptive statistical analysis with the percentage formula. The results showed that the level of physical fitness of class X students at Pembangunan V Yapis Waena High School varied. A total of 11 students (52.38%) have a physical fitness level at a moderate level. Found 7 students (33.33%) have a physical fitness level at a good level. There were 3 students (14.28%) had a physical fitness level at a poor level. The distribution profile of physical fitness levels shows that the majority of class X students have good fitness levels, but there are still some students who have low fitness levels. This shows the importance of efforts to increase student participation in physical activities and sports at school. Based on the results of this study, it is recommended that schools make further efforts to increase student participation in physical activities and sports. Interesting and diverse sports programs can be designed to encourage students to be more physically active and maintain their health